1993
DOI: 10.1111/j.1365-2958.1993.tb01229.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeat sequences in the Bordetella pertussis adenylate cyclase toxin can be recognized as alternative carboxy‐proximal secretion signals by the Escherichia coliα‐haemolysin translocator

Abstract: The 1706-residue adenylate cyclase toxin (CyaA) of Bordetella pertussis is an RTX protein with extensive carboxy-proximal glycine and aspartate-rich repeats. CyaA does not have a cleavable amino-terminal signal peptide and can be secreted across both bacterial membranes of the Escherichia coli cell envelope by the alpha-haemolysin (HlyA) translocator (HlyBD/TolC). We performed deletion mapping of secretion signals recognized in CyaA by this heterologous translocator. Truncated proteins with N-terminal and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
73
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 47 publications
1
73
0
Order By: Relevance
“…Another common trait of RTX proteins is their special single-step translocation mechanism across both the inner and outer membranes via a type I secretion system, initiated by a C-terminal secretion signal (189,190).…”
Section: Rtxc Acyltransferases That Activate Rtx Leukotoxinsmentioning
confidence: 99%
“…Another common trait of RTX proteins is their special single-step translocation mechanism across both the inner and outer membranes via a type I secretion system, initiated by a C-terminal secretion signal (189,190).…”
Section: Rtxc Acyltransferases That Activate Rtx Leukotoxinsmentioning
confidence: 99%
“…Indeed, it contains a pore-forming domain (from residues 500 -700) with four hydrophobic segments (17,18,22,23), the target site for the post-translational palmitoylation (7,24), 30 -40 copies of a characteristic glycine-and aspartate-rich nonapeptide repeats (residues 1006 -1613) of the prototype GGXG(N/ D)DX(U)X (X represents any amino acid, and U represents any large hydrophobic residue such as Ile, Leu, Val, Phe, Tyr), representing the main calcium-binding sites of the protein (25) (see Fig. 1), and a nonprocessed C-terminal secretion signal (4,26). The crystal structure of the Pseudomonas aeruginosa alkaline protease that has six of these consensus RTX repeats revealed that these sequences constitute a new kind of calcium binding structure, called a parallel ␤-helix or parallel ␤-roll motif (27,28).…”
mentioning
confidence: 99%
“…Such blocks of repeats, which define the so-called RTX toxins (24), can occur variously from 70 to 150 residues from the C terminus, and the number of RTX repeats can also vary from 5 to 7 to up to at least 33. In several cases, in addition to HlyA, direct evidence for the presence of a C-terminal secretion signal has been obtained (3,8,17,21,26,27). Moreover, albeit with various degrees of efficiency, translocators can be exchanged and secretion of heterologous toxins or proteases can be demonstrated, with the E. coli HlyBD translocator being particularly promiscuous in this respect (see, for example, references 3, 4, 11, 20, and 26).…”
mentioning
confidence: 99%
“…All previous mutagenesis studies have concentrated upon the terminal 50 to 60 amino acids in attempts to localize the HlyA secretion signals, although the most proximal N-terminal boundary of the signal has not been established. In the related cyclolysin, different sequences capable of targeting the protein to the medium have been localized in at least the last 100 C-terminal residues (21). In order to test the possibility that the secretion signal(s) extended beyond the C-terminal 46 residues identified previously in HlyA (15,22), we sought to isolate mutations within the terminal 149 residues by using random mutagenesis.…”
mentioning
confidence: 99%